Public Private Partnership in National Highways Model Concession Agreement Fourth Edition: April 2014 - Planning Commission (Planning Commission, 2014)
There is today a broad consensus that a sustained growth rate of about 8% per annum is the minimum necessary if India is to eliminate poverty and achieve a quantum jump in the quality of life of its citizens. One of the preconditions for sustaining such a growth rate is the creation of world class infrastructure. The quality of our infrastructure, at present, simply will not allow the economy to reach the level of competitiveness needed to achieve 8% growth in an open economy. However, the investment requirement for meeting the infrastructure deficit is such that it cannot possibly be met by relying on the public sector alone.
Planning Commission Government Of India
Planning Commission Government of India